What Works (or Does Not) in Community Risk Management for Persons Convicted of Sexual Offenses? A Contemporary Perspective - Wilson, Robin J. (International journal of offender therapy and comparative criminology, 2021)
Contemporary data from the United States show that rates of sexual offending and reoffending have been in steady decline for decades. Nonetheless, nonprofessionals continue to view sexual violence as a community safety issue fraught with risk and uncertainty. The past 30 years have been witness to considerable research and practice in the assessment, treatment, and risk management of persons who have sexually offended. Gains have also been made in regard to prevention and citizen education. Modern day technologies include actuarial risk assessment instruments, measures of criminogenic need and treatment progress, refinements to treatment processes, and the establishment of evidence-based models. Legislative authorities in the United States and elsewhere have also attempted to affect risk in the community with, perhaps, lesser degrees of success. This article reviews current policies and practices, with a specific focus on what happens when offenders are released to the community (e.g., how public policies intended to track offenders and/or restrict their movements can negatively affect community reintegration). Comprehensive approaches to community sexual offender management are examined in addition to suggestions of unique approaches intended to ensure citizen buy-in and engagement.